OPTIMIZING PRODUCTION PROCESS BY INTEGRATING 3D MANUFACTURING TECHNOLOGY USING AUTODESK INVENTOR SOFTWARE TO IMPROVE EFFICIENCY - Chandra, Muhammad Ali; Isminarti, Isminarti; Fauziah, Fauziah; Mulyadi, Yahya Bin; Abas, Mohamad Ilyas (Universitas Muhammadiyah Gorontalo, 2024)
The concepts of efficiency and quality represent pivotal dimensions within contemporary manufacturing sectors. The amalgamation of manufacturing technology with design software, alongside the deployment of 3D scanning technology, is instrumental in the realization of these objectives, particularly within the framework of Industry 4.0. This investigation delves into the synthesis of manufacturing technology with design software and the utilization of 3D scanning technology in relation to Industry 4.0. More precisely, this research seeks to ascertain the most recent innovations in technology integration while assessing the advantages and obstacles associated with 3D scanning technology in the manufacturing domain. A methodological approach encompassing a literature review in conjunction with case studies is employed. Case studies were executed at PT. Metalindo Teknik Utama, a manufacturing entity, to examine the practical implications of technology integration.Qualitative analysis is used to identify patterns and critical findings. The study reveals significant advancements in technology integration, particularly in CAD, CAM, IoT, and IIoT, contributing to increased production efficiency and responsiveness to market changes. Additionally, Autodesk Inventor applications show potential in enhancing product design, evaluation, and production processes. These findings suggest that the integration of technology with design software and the adoption of 3D scanning technology have the potential to revolutionize the manufacturing process, improving efficiency and quality. This study emphasizes the importance of integrating manufacturing technology with design software and adopting 3D scanning technology in the manufacturing industry. Insights gained from this research provide valuable guidance for industry practitioners in optimizing production processes and remaining competitive in the era of Industry 4.0.